1996
DOI: 10.3758/bf03201101
|View full text |Cite
|
Sign up to set email alerts
|

Information processing during general anesthesia: Evidence for unconscious memory

Abstract: Memory for words presented during general anesthesia was studied in two experiments. In Experiment 1,surgical patients (n = 80) undergoing elective procedures under general anesthesia were presented shortly before and during surgery with words via headphones. At the earliest convenient time after surgery (within 5 h) and 24 h later, memory was tested by asking patients to complete auditorily presented word stems with the first word that came to mind and to leave out words they remembered having heard earlier (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…Bovill, & Zwaveling (1988) .12 53 Bonke, Schmitz, Verhage, & Zwaveling (1986) .06 55 Caseley-Rondi, Merikle, & Bowers (1994) Ϫ.11 96 De Houwer, Demeyere, Verhamme, & Eelen (1995) a .18 40 Evans & Richardson (1988) .50 39 Furlong & Read (1993) Ϫ.13 108 Jelicic, .10 82 Korunka, Guttmann, Schleiitz, Hilpert, Haas, & Fitzal (1992) .03 108 Liu, Standen, & Aitkenhead (1992) Ϫ.13 48 Liu, Standen, & Aitkenhead (1993) .14 82 Pearson (1961) .28 81 Steinberg, Hord, Reed, & Sebel (1993) .19 60 Van der Laan, van Leeuwen, Sebel, Winograd, & Bonke (1996) .13 40 Woo, Seltzer, & Marr (1987) . 20 Caseley-Rondi, Merikle, & Bowers (1994) .23 74 McClintock, Aitken, Downie, & Kenny (1990) .29 60 Steinberg, Hord, Reed, & Sebel (1993) .20 60 Van der Laan, Van Leeuwen, Sebel, Winograd, Bauman, & Bonke (1996) Ϫ.04 40 Charlton, Wang, & Russell (1993) .15 44 Cork, Kihlstrom, & Schacter (1992) Ϫ.14 25 De Roode, Jelicic, Bonke, & Bovill (1995) Ϫ.08 83 Donker, Phaf, Porcelijn, & Bonke (in press) .09 58 Jelicic, Bonke, Wolters, & Phaf (1992) .29 50 Jelicic, De Roode, Bovill, & Bonke (1992) .48 43 Khilstrom, Schacter, Cork, Hurt, & Behr (1990) .31 25 Roorda-Hrdlickova, Wolters, Bonke, & Phaf (1990) .59 81 Villemure, Plourde, Lussier, & Normandin (1993) .54 10 Westmoreland, Sebel, Winograd, & Goldman (1993) .08 48 Direct measures Bonebakker, Bonke, Klein, Wolters, Stijnen, Passchier, & Merikle (1996) .24 160 Block, Ghoneim, Sum Ping, & Ali (1991b) .06 72 Dwyer, Bennett, Eger, & Peterson (1992) .00 45 Humphreys, Asbury, & Millar (1990) Ϫ.13 20 Jelicic, Asbury, .04 …”
Section: Discussionmentioning
confidence: 99%
“…Bovill, & Zwaveling (1988) .12 53 Bonke, Schmitz, Verhage, & Zwaveling (1986) .06 55 Caseley-Rondi, Merikle, & Bowers (1994) Ϫ.11 96 De Houwer, Demeyere, Verhamme, & Eelen (1995) a .18 40 Evans & Richardson (1988) .50 39 Furlong & Read (1993) Ϫ.13 108 Jelicic, .10 82 Korunka, Guttmann, Schleiitz, Hilpert, Haas, & Fitzal (1992) .03 108 Liu, Standen, & Aitkenhead (1992) Ϫ.13 48 Liu, Standen, & Aitkenhead (1993) .14 82 Pearson (1961) .28 81 Steinberg, Hord, Reed, & Sebel (1993) .19 60 Van der Laan, van Leeuwen, Sebel, Winograd, & Bonke (1996) .13 40 Woo, Seltzer, & Marr (1987) . 20 Caseley-Rondi, Merikle, & Bowers (1994) .23 74 McClintock, Aitken, Downie, & Kenny (1990) .29 60 Steinberg, Hord, Reed, & Sebel (1993) .20 60 Van der Laan, Van Leeuwen, Sebel, Winograd, Bauman, & Bonke (1996) Ϫ.04 40 Charlton, Wang, & Russell (1993) .15 44 Cork, Kihlstrom, & Schacter (1992) Ϫ.14 25 De Roode, Jelicic, Bonke, & Bovill (1995) Ϫ.08 83 Donker, Phaf, Porcelijn, & Bonke (in press) .09 58 Jelicic, Bonke, Wolters, & Phaf (1992) .29 50 Jelicic, De Roode, Bovill, & Bonke (1992) .48 43 Khilstrom, Schacter, Cork, Hurt, & Behr (1990) .31 25 Roorda-Hrdlickova, Wolters, Bonke, & Phaf (1990) .59 81 Villemure, Plourde, Lussier, & Normandin (1993) .54 10 Westmoreland, Sebel, Winograd, & Goldman (1993) .08 48 Direct measures Bonebakker, Bonke, Klein, Wolters, Stijnen, Passchier, & Merikle (1996) .24 160 Block, Ghoneim, Sum Ping, & Ali (1991b) .06 72 Dwyer, Bennett, Eger, & Peterson (1992) .00 45 Humphreys, Asbury, & Millar (1990) Ϫ.13 20 Jelicic, Asbury, .04 …”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that pre-existing knowledge may be activated during general anaesthesia and unconscious learning may take place [34]. Block et al used a word completion test [35] and Bonnebakker et al used a forced choice recognition test [36] to also demonstrate the possibility of unconscious learning during general anaesthesia.…”
Section: Subconscious Perception With Implicit Memorymentioning
confidence: 99%
“…Similarly, a review by Johnston and Dark (1986) on selective attention also has shown that a semantic analysis of words presented in a secondary channel only occurs if the words have significant relevance to the subject. There is also research on memory under general anaesthesia (e.g., Andrade, 1995;Bennett, 1993;Bonebakker, et al, 1996;Kihlstrom, and Couture, 1992;Kihlstrom, Schacter, Cork, Hurt and Behr, 1990;Merikle and Daneman, 1996) with some suggesting that only personally meaningful events heard in the operating room while a patient is under general anaesthesia are able under certain conditions to be later recalled (Andrade, 1995).…”
Section: Significant Variablesmentioning
confidence: 99%